The culture inoculation method could influence heavy metals levels in soil, plant uptake, and biomass: a meta-analysis - Taufiq Bachtiar; Ratih Nurjayati; Ania Citraresmini; Hidawati Hidawati; Veny Rachmawati; Asep Mulyono; Rhazista Noviardi; Wilda Naily; Merri Jayanti; Siti Wahyuningsih; Dyah Marganingrum; Muhammad Rahman Djuwansyah; Mohd Noor Hidayat Adenan (Universitas Sebelas Maret, 2025)
Heavy metals (HMS) contamination in soil is a major issue that significantly impacts plants and human health. Various approaches have been employed to mitigate the effects of heavy metals, including the application of microorganisms (MO). This study aims to analyze the impact of bioinoculation application on HMS content in plants and soil through a meta-analysis approach. Twenty-nine publications reviewed between 2001 and 2023 reported the effects of microorganism applications on HMS content in plants and soil. A systematic review was applied to select relevant studies, and effect sizes (ES) were calculated using Hedges’d to quantify the impact of microbial treatments on heavy metal content. The parameters observed were As, Hg, Cd, Cr, Ni, Co, Pb, Ni, Mn, Zn, and Fe in plants (shoots, roots, fruit, and total plants), soil, and plant biomass. The ES values of Hedges’ microorganisms HMS on soil, plants, and plant biomass were -3.257 (p<0.001), 1.234 (p<0.001), and 2.301 (p<0.001), respectively. The results showed that the greatest reduction in HMS content in the soil was the combined application of fungi and bacteria (ES -5.519; p<0.001), and the highest metal content absorbed by the soil and plants was Cu (ES -13.642; p<0.001) and Pb (2.645; p<0.001), respectively. This study showed that Orychophragmus violaceus had the highest metal absorption rate (ES 15.528, p<0.001) to help clean up heavy metal contamination, especially in agricultural land and industrial areas. This approach can improve soil quality, enhance plant growth, and reduce health risks, which benefits farmers, policymakers, and environmental agencies.